Association of pro-inflammatory diet with increased risk of gallstone disease: a cross-sectional study of NHANES January 2017–March 2020 - Cheng, Jinnian; Zhuang, Qian; Wang, Weiyi; Li, Ji; Zhou, Lu; Xu, Ying; Zhang, Haiqin; Zhang, Zixu; Zhou, Fengli; Yang, Daming; Chu, Yimin; Peng, Haixia (Frontiers in Nutrition, 2024)
Background and aim: Gallstone disease (GSD) is a major public health problem worldwide. The dietary inflammatory index (DII) and the energy-adjusted DII (E-DII) have been used to describe dietary inflammatory potential. The current study sought to investigate the pro-inflammatory role of diet on GSD among outpatients in the United States.Methods: Cross-sectional data from 7,334 individuals older than 20 years who participated in the National Health and Nutrition Examination Survey (NHANES) from January 2017 to March 2020 were obtained. The relationship between GSD and DII was assessed using self-reported data. An association between DII and the risk of GSD was determined using sample-weighted logistic regression and restricted cubic splines (RCS). Subgroup analyses were conducted to assess the interaction between DII and related factors. Sensitivity analysis was further used to confirm the stability of the relationship. To control for the effect of total energy intake, the energy-adjusted DII (E-DII) was calculated and analyzed.Results: A total of 10.5% of the study participants had GSD. The DII ranged from -5.52 to 5.51, and the median DII was significantly higher for participants with GSD than those without (1.68 vs 1.23, P <0.001). There was a significant and stable positive relationship between DII and GSD in adjusted models (OR 1.10, 95% CI 1.00-1.20).In the fully adjusted model, subjects with DII scores in the highest tertile were more likely to have GSD than those in the lowest tertile (OR 1.52,). An apparent dose-response association between DII and GSD was detected. The association between E-DII and GSD remained stable.Higher DII/E-DII scores linked to the intake of a pro-inflammatory diet were positively associated with a higher risk of GSD. These findings suggest that proinflammatory dietary patterns can promote the formation of gallstones.